Analysis of the springback effect of laser welded DP600 high-strength steel thin sheets - Almeida, Christyane Oliveira Leão [UNESP]; Santos, Odair José Pereira dos [UNESP]; Panziera, Renato Camponogara; Dutra, Manoel Kolling; Pereira, Milton; Pereira, Marcelo dos Santos [UNESP] (Laser Institute of America, 2023)
Steel sheets are produced with increasingly smaller thicknesses, without compromising the properties of the steel, maintaining ductility, strength, and energy absorption after impact can total depth enhance vehicle energy efficiency, lower manufacturing costs, and address the springback effect. The springback effect of laser-welded DP600 two-phase steel sheets was studied in this research. Parameters such as punching speed, initial bending angle, and time were varied. Tests including tensile tests, Vickers hardness, and optical microscopy analysis were conducted to correlate results with material properties. Autogenous laser welding joined DP600 steel plates at the bending position. Controlling springback ensures better quality in vehicle manufacturing and assembly. The results revealed that increasing the punch descent speed from 4 to 12 mm/min, for an internal angle of 90°, on the first day of observation, led to higher springback values (0.58°-3.3°, respectively), while increasing the initial curvature angle (30°-90°), maintaining a constant speed of 4 mm/min on the first day of observation, and impacting the elastic return (6.74°-0.58°, respectively). Furthermore, the observation time demonstrated a continuous increase in the springback variation during 6 days after the flexural test before stabilization (6.89°- 8.7°), maintaining a constant value of 8 mm/min and the internal angle of doubles of 30°.
Keywords: high strength steel-DP600; laser welding; springback effect; tailored welded blanks.